Understanding the impact of neoadjuvant chemoradiation on health-related quality of life in esophageal cancer - Semenkovich, Tara R.; Meyers, Bryan F. (Video-Assisted Thoracic Surgery, 2018)
In the recent manuscript “Effect of neoadjuvant chemoradiotherapy on health-related quality of life in esophageal or junctional cancer: results from the randomized CROSS trial”, Noordman et al. (1) compared health-related quality of life (HRQOL) outcomes between two groups of patients: those randomized to neoadjuvant chemoradiation (nCRT) followed by surgery and those treated with surgery alone for esophageal cancers.